A Warm Water Pool-Based Exercise Program Decreases Immediate Pain in Female Fibromyalgia Patients: Uncontrolled Clinical Trial - Segura-Jiménez, V.; Carbonell-Baeza, A.; Aparicio, V. A.; Samos, B.; Femia, P.; Ruiz, J. R.; Delgado-Fernández, M. (International Journal of Sports Medicine, 2013)
Fibromyalgia is characterized by chronic and extended musculoskeletal pain. The combination of exercise therapy with the warm water may be an appropriate treatment. However, studies focusing on the analysis of immediate pain during and after an exercise session are rare. This study aimed to determine the immediate changes of a warm water pool-based exercise program (12 weeks) on pain (before vs. after session) in female fibromyalgia patients. 33 Spanish women with fibromyalgia were selected to participate in a 12 weeks (2 sessions/week) low-moderate intensity warm water pool-based program. We assessed pain by means of a Visual Analogue Scale before and after each single session (i. e., 24 sessions). We observed immediate benefits on pain with a mean decrease ~15% in all sessions, except in the fourth one. There was an association of pain difference (pre-post) session with pain pre session (p=0.005; β=0.097±0.034) and with age (p<0.001; β=0.032±0.008). There were no significant accumulative differences on pain, pre session, post session, and pre-post changes (all p>0.05). Therefore this study showed that a warm water pool-based exercise program for 12 weeks (2 times/week) led to a positive immediate decrease in level of pain in female patients with fibromyalgia. Improvements were higher in older women and in those with more intense pain.
Keywords: immediate pain; fibromyalgia; women; exercise therapy; pool-based; warm water